Intervención fisioterapéutica en paciente masculino de 88 años de edad con gonartrosis o artrosis de rodilla. - Cisneros Muñoz, Janela Lisbeth (2024)
The following is the case of an 88-year-old man with knee gonarthrosis, a chronic degenerative disease affecting the knee joint. Symptoms include pain, stiffness, swelling and limitation of motion. The diagnosis is confirmed by clinical and radiographic findings. Patient treatment involves pharmacological measures such as analgesics and anti-inflammatory drugs, along with non-pharmacological therapies such as physiotherapy, occupational therapy and environmental adjustments. Physiotherapy plays an essential role in the management of gonarthrosis, with therapeutic exercises, physical modalities and manual therapy to mitigate pain, improve joint function and strengthen the musculature. The clinical case was examined in detail to evaluate the efficacy of the physiotherapeutic intervention in the patient. The follow-up of the treatment evidences a significant improvement in the patient's pain, mobility and quality of life, highlighting the importance of a comprehensive and personalized approach in the management of gonarthrosis. Among the recommendations, it is suggested to continue with the exercise program and manual therapy, maintain an adequate body weight and receive ongoing education on disease management. Regular medical follow-up is crucial to assess disease progression and adjust the treatment plan as needed.